A in vitro study on the effect of tensile bond strength of visible light activated resin to enamel using 5, 15 and 45 secs. washing times etched with gel and aqueous etchants - Dy, Christine; Hermano, Kathleen; Medina, Vicente (Adviser).
The acid etch technique has long been introduced by Buonocore since 1955 to enhance bonding of resin to tooth surface. Washing the etched surface has been found to greatly improve the bond strenght between resin and tooth. This study evaluated the effects of 5,15 and 45 secs. washing times using gel and aqueous etchants on 60 freshly extracted maxillary anterior teeth. With the gel etchant, bond strength of Visible Light Activated Composite (VLAC) resin to tooth was not greatly affected by washing time. Whereas, with aqueous etchant, bond strength increased directly as washing time was prolonged. Comparing the bond strengths using gel with that of aqueous etchant revealed that at 5 secs. and 45 secs. washing times, teeth etched with aqueous phosphoric acid exhibited a higher bond strength than those treated with gel etchant. At 15 secs. washing time, no significant difference was demonstrated.
Seminar Paper--Doctor of Dental Medicine--University of the Philippines Manila.